Multivariate analysis of Co, Fe and Ni leaching from tailings following simulated temperature change - Fu, Shuai; Lu, Jinmei; Yuan, Fuqing (IOP Conference Series: Earth and Environmental Science, 2018)
Published version available at: https://iopscience.iop.org/article/10.1088/1755-1315/191/1/012125/pdf A series of column leaching experiments were performed to understand the leaching behavior of Co, Fe and Ni in Ballangen mine tailings. Multivariate statistical approaches to evaluate potential risk variations in leachate quality and identifies temperature effects on their leaching behavior. Results from column leaching test indicated that the mobility of showed higher temperature may encourage oxidation and sulfuration in tailings that promoted heavy metal release from tailings through runoff and erosion. Ni and Co have the similar resource from tailings and positive correlation in the leaching activity. The leaching of Fe was closely related to temperature change and affected the leaching of other metals. Temperature, however, increased risk of heavy metal leaching from tailings by temperature change should be caught more attention.